Chikungunya virus: an update on the biology and pathogenesis of this emerging pathogen - Burt, Felicity J; Chen, Weiqiang; Miner, Jonathan J; Lenschow, Deborah J; Merits, Andres; Schnettler, Esther; Kohl, Alain; Rudd, Penny A; Taylor, Adam; Herrero, Lara J; Zaid, Ali; Ng, Lisa F P; et al. (The Lancet infectious diseases, 2017)
Re-emergence of chikungunya virus, a mosquito-transmitted pathogen, is of serious public health concern. In the past 15 years, after decades of infrequent, sporadic outbreaks, the virus has caused major epidemic outbreaks in Africa, Asia, the Indian Ocean, and more recently the Caribbean and the Americas. Chikungunya virus is mainly transmitted by Aedes aegypti mosquitoes in tropical and subtropical regions, but the potential exists for further spread because of genetic adaptation of the virus to Aedes albopictus, a species that thrives in temperate regions. Chikungunya virus represents a substantial health burden to affected populations, with symptoms that include severe joint and muscle pain, rashes, and fever, as well as prolonged periods of disability in some patients. The inflammatory response coincides with raised levels of immune mediators and infiltration of immune cells into infected joints and surrounding tissues. Animal models have provided insights into disease pathology and immune responses. Although host innate and adaptive responses have a role in viral clearance and protection, they can also contribute to virus-induced immune pathology. Understanding the mechanisms of host immune responses is essential for the development of treatments and vaccines. Inhibitory compounds targeting key inflammatory pathways, as well as attenuated virus vaccines, have shown some success in animal models, including an attenuated vaccine strain based on an isolate from La Reunion incorporating an internal ribosome entry sequence that prevents the virus from infecting mosquitoes and a vaccine based on virus-like particles expressing envelope proteins. However, immune correlates of protection, as well as the safety of prophylactic and therapeutic candidates, are important to consider for their application in chikungunya infections. In this Review, we provide an update on chikungunya virus with regard to its epidemiology, molecular virology, virus-host interactions, immunological responses, animal models, and potential antiviral therapies and vaccines.